COMPARATIVE ANALYSIS OF ORGODONTIC ALIGNERS AND BRACKET SYSTEMS - Сергей Владимирович Черненко; Ольга Сергеевна Корчемная; Владимир Маркович Корчемный; Елена Александровна Киселева; Светлана Ивановна Елгина; Елена Владимировна Рудаева; Кира Борисовна Мозес; Яэль Центер (Медицина в Кузбассе)
The use of transparent aligners is one of the methods of orthodontic treatment. Transparent aligners are an aesthetic and convenient option for orthodontic treatment, and have gained huge popularity. In recent years, we have seen an increase in the number of adult patients coming for orthodontic treatment. As the demand for aesthetic treatment grows, more and more people are looking for alternatives to fixed orthodontic braces. Transparent aligners move teeth somewhat differently than fixed equipment. The use of aligners makes it possible to eliminate some occlusion anomalies more effectively than fixed equipment, providing vertical control and better support. The study allowed us to conduct a quantitative analysis of the use of modern orthodontic systems (braces and aligners) for the treatment of dental anomalies, the distribution of patients by age and gender when using these methods of treatment in residents of the Kemerovo region.